PROSES TIM SOCIAL MEDIA DALAM PUBLIKASI KONTEN SOCIAL MEDIA INSTAGRAM PRODUCTION HOUSE AMADEUS SINEMAGNA - Muhammad Nauval Faturachman; Yusalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the roles and workflow of the social media team in publishing Instagram content at the production house Amadeus Sinemagna, as well as to uncover the challenges encountered during the process. Using a descriptive qualitative method, data were collected through participatory observation, interviews, and literature review. The findings indicate that the publication process consists of three main stages: pre-production, production, and post-production. These stages involve content planning, visual production, caption writing, and scheduled distribution. The challenges identified include repeated revisions, inefficient team coordination, technical issues, and delays in content approval. These findings highlight the importance of a well-structured workflow and cross-functional collaboration in optimizing digital content production.